Beyond the bari: Gender, groups, and social relations in rural Bangladesh - Quisumbing, Agnes R. (International Food Policy Research Institute, 2009)
This paper uses a longitudinal data set from rural Bangladesh to analyze the factors that affect men's and women's ability to participate in groups and to engage in relationships with powerful and influential people. Unlike studies from other countries that find group membership to be positively correlated with wealth, this study finds that group membership, which is driven mostly by women's membership in NGOs, is progressive, with higher participation rates among the poor and those with smaller sizes of owned land. This is in large part due to the targeting mechanism and pro-poor orientation of NGOs. In contrast to group membership, however, the strength of relationships with most types of influential persons increases with human and physical wealth. Consistent with a collective model of household decision-making, husband's and wife's human and physical assets do not have the same influence on group membership and relationship strength. Indicators of relative bargaining power within marriage also have differential effects on group membership and social relations. Women who bring more assets to marriage, who live closer to their natal villages, and who have sons are more likely to belong to a group. Assets at marriage and distance to village of husbands and wives also have differential effects on relationship strength, indicating that spouses may not share the same preferences nor pool their resources when investing in relationships with powerful and influential people.